PERLINDUNGAN HUKUM MENGENAI KEBOCORAN DATA PRIBADI TERHADAP AKUN MICROSOFT OFFICE 365 YANG DIBELI MELALUI SHOPEE - Agustinus Astono (Penerbit Universitas Atma Jaya Yogyakarta, 2022)
In the new era, commonly referred to as big data, online-based storage is increasingly needed to accommodate data and information obtained and sent. The problem is that many users of Microsoft 365 series accounts are purchased illegally from sellers on the Shopee site and do not realize sellers have access to synchronize user data. The data is connected online and automatically, especially in data storage applications from the Microsoft 365 series, namely OneDrive so it can pose a significant threat to personal information leakage. This article aims to dissect and obtain an ideal concept regarding protecting the personal data of Microsoft Office 365 users purchased through the Shopee site. A legal study is a normative study of applicable legal provisions or statutory regulations. The result shows that the explicit rules in the new Personal Data Protection Law related to Cloud Computing Systems, as well as preventive measures to avoid leakage of personal data using self-literacy on the importance of protecting personal data. For example, customers should use a secure site for online transactions, stop buying products or application accounts online illegally, and use security antivirus software.